2019
DOI: 10.1063/1.5108815
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric diagnostic in the synthesis of carbon nanostructures via submerged arc discharge: Stability, nucleation and yield

Abstract: Submerged arc discharge (SAD) is a simple method to produce carbon nanostructures (CNSs). However, its potential cannot be fully exploited because it generates contaminants and unwanted by-products (CUBPs) that are difficult to eliminate. The formation mechanisms of CNSs and CUBPs were investigated by measuring the correlations between the SAD main parameters (current, voltage, power, anode displacement, and sound emission). It was demonstrated that the SAD takes place in a succession of stable and unstable zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…As determined by prior studies through N 2 adsorption (Brunauer-Emmett-Teller) BET isotherms our CNOs rich SADW floating material exhibits no microporosity, an almost total absence of surface defects and a very modest specific surface area (SSA) of 14.7±0.3 m 2 g −1 [21]. A thorough characterisation of the SADW CNOs produced by our research group can be found in previously published articles [21,34,[41][42][43][44].…”
Section: Resultsmentioning
confidence: 86%
“…As determined by prior studies through N 2 adsorption (Brunauer-Emmett-Teller) BET isotherms our CNOs rich SADW floating material exhibits no microporosity, an almost total absence of surface defects and a very modest specific surface area (SSA) of 14.7±0.3 m 2 g −1 [21]. A thorough characterisation of the SADW CNOs produced by our research group can be found in previously published articles [21,34,[41][42][43][44].…”
Section: Resultsmentioning
confidence: 86%
“…The functional groups present in these nanostructures ensure a high stability of this suspension. The precipitate has a more complex composition, being a mixture of nanostructures (MWCNTs, CNOs, and graphene) (1.4323 g, see figure 1(c)) and contaminants (amorphous carbon, nano, and micro graphite) [15]. Aggregates are also present in the precipitate [16] (see figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…As analysed in [15], the SADW arc discharge process consists of a succession of slow-burning stable periods and high-erosion unstable periods called stable zones (SZ) and unstable zones (UZ), respectively. SZs were defined as periods where R 1 mg.s −1 , and UZs were defined as the periods where R > 1 mg.s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ref. [29] reported on the relation between arc sound and other physical-chemical processes in SAD. The authors simultaneously recorded the arc current, voltage, and sound plus the anode displacement in a correlated manner.…”
Section: Merits and Disadvantages Of The Stabilization Methodsmentioning
confidence: 99%
“…Therefore, different values of flexural strength and thermal and electrical conductivities, among other parameters, can be observed in different electrode zones [28]. This factor is one of the causes that make the SAD technique unfree of contaminants [29].…”
Section: Electrode Heterogeneitymentioning
confidence: 99%